Literature Review study of Data Replication Methods in Distributed Systems - Sherina Intania; Hetty Rohayani (International Journal of Innovation Research in Education, Technology and Management, 2025)
This research discusses data replication methods in distributed systems, which is an important requirement in modern data processing. The purpose of the research is to explore effective replication methods in distributed systems, such as synchronous, asynchronous, multimaster, partial replication, bidirectional replication, replication with load balancing, replication with auto-promote and replication with web services. As well as the challenges faced in maintaining data consistency. The method used is Systematic Literature Review (SLR) by analyzing 15 related scientific journals on best practices in data replication methods in distributed systems. The results show that there are 3 replications that are considered best practices, namely multimaster replication applied in the payroll system at CV Rejeki Jaya Makmur Abadi, synchronous replication in the online KRS application at Jabal Ghafur University, and asynchronous replication applied to the Graha Manunggal Property and Dealand Property financial systems. synchronous replication ensures data consistency with a 100% success rate, while asynchronous offers flexibility in transactions despite connection disruptions and multimaster replication provides high availability and operational efficiency. This research is expected to provide insight for distributed system developers to choose the replication method that best suits the needs of the application.